The Application of Finger Grip Therapy to Reduce Pain in Postoperative Patients in the Wijaya Kusuma Bawah Ward of Kardinah Regional General Hospital, Tegal City - Anjani, Meti; Fadila, Erida; Syaripudin, Ahmad (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Postoperative pain is a physiological response that patients can feel. Non-pharmacological pain management that can alleviate pain includes finger grip relaxation therapy. Finger grip relaxation techniques involve finger gripping and breath control. Energy flow is perceived as a stimulus for relaxation; reflex points on the hands provide reflex stimulation during the grip, and this stimulation redirects electrical waves to the brain, which processes them and transmits them to the nerves in the affected body organs. This study aims to investigate the application of finger grip therapy in reducing post-operative pain in the Wijaya Kusuma Bawah Ward of Kardinah General Hospital in Tegal City. Method: A descriptive method was used with the application of case study results. Result: Finger grip therapy was applied for 3 days to patients with post-debridement lymphadenopathy experiencing acute pain. The study showed that subjects experienced moderate pain before receiving finger grip therapy, and after the therapy, patients experienced a reduction in pain to mild pain. Conclusion: In this study, finger grip therapy was effective in reducing pain levels in post-operative patients.